Chronicle: Academician Leonid Maksimovich Brekhovskikh – 100th Anniversary of the Birth - SEREBRYANY, Andrey N. (Archives of Acoustics, 2018)
Biography and scientific achievements of Academician Leonid Maksimovich Brekhovskikh - Russian physicist, the founder of the scientific school of Ocean Acoustics, Doctor of Physics and Mathematics Sciences, Professor, Academician of the Russian Academy of Sciences.